MARTABAT TUJUH SEBUAH ONTOLOGI SUFI - Baharuddin AbdRahman (DIRASAT: Jurnal Studi Islam dan Peradaban, 2018)
The controversy surrounding waḥdat al-wujūd vs waḥdat al-syuhūd is still considered to be perennial, especially in the ṣūfī circle. This study is an exposition of the seven degree of existences (marātib al-wujūd) from the perspective of al-Makassarī. Using the literature study, this research succeeded in structuring the dignity wujūd as follows: first Dhāt al-Ḥaq, second al-Waḥdah, third al-Wāḥidiyyah, fourth al-Arwaḥ, fifth al-Mitsal, sixth al-Syahādah, and seventh al-Insān al-Kāmil.